2. CLINICAL AND SUBCLINICAL CHARACTERISTICS OF MULTIPLE MYELOMA PATIENTS (Vietnam Journal of Community Medicine, 2023)
Objectives: To describe the clinical and subclinical characteristics of patients with multiplemyeloma. Subjects and methods: A retrospective and prospective descriptive study on 96 patientswith multiple myeloma diagnosed, treated and autologous stem cell transplantation at the Ho ChiMinh City Blood Transfusion Hematology Hospital from 2018 to 2021. Results: The most commonform of multiple myeloma was monoclonal IgG (62.8%), followed by IgA monoclonal increase(18.75%) and light chain (18.75%). The group of multiple myeloma patients in stage II accountedfor the highest percentage (69.8%), followed by stage I (18.7%). The number of patients hospitalizedin stage III accounted for the lowest rate (11.5%). The mean hemoglobin concentration was 94.1 ±20.4 (g/l), white blood cell count (6.42 ± 2.38 G/l), platelet count (186.4 ± 75.3 G/l) l), bone marrowcell count (71.16 ± 68.7 G/l), percentage of plasma cell lineage in the marrow (35.6 ± 21.3 %). IgG(6281.0 ± 2938.6 mg/L), IgA (3521.4 ± 1405.3 mg/L), Free Kappa (1201.5 ± 1422.1), Free Lambda(2194.7 ± 2421) ,1), ß2 microglobulin (4.24 ± 6.67 mg/L). Conclusion: The most common type ofmultiple myeloma was monoclonal IgG. The group of patients with multiple myeloma in stage IIaccounted for the highest percentage.
Keywords: Multiple myeloma, clinical and subclinical characteristics.